Pride the story of the LGBTQ equality movement - Todd, Matthew (Welbeck, 2021)
For 50 years, people have flocked to San Francisco for the annual Pride Parade, a beloved event that serves as a celebration and demonstration for legal rights such as same-sex marriage. Pride explores the history of the LGBTQ movement including events such as Stonewall and the global explosion in Pride Parades, and is a comprehensive account of the ongoing challenges facing the LGBTQ community. Pride documents the milestones in the fight for equality, from the victories of early activists, to the gradual acceptance of the LGBTQ+ community in politics, sports, and the media and the landmark court cases that helped to ban discrimination, permit marriage, and help in the fight for equality